Rehabilitation of missing digit using customized attachment supported prosthesis - Siddharth Mehta; Rasalika Agrawal; Shashank Chitikeshi; D B Nandeeshwar (Wolters Kluwer Medknow Publications, 2019)
Traumatic amputation of a finger leads to psychological instability, functional loss, and poor esthetics. When surgical reconstruction in patients is not possible, prosthesis provides psychological, functional, rehabilitative, and esthetic restoration. Despite the availability of advanced skills, the best of materials and laboratory support, sometimes the anatomy of the defect, may be a hindrance in furnishing a better prosthesis. In the present case report, a defect with complete loss of stump was restored using customized ring-stump assembly, which helped to enhance the fit and retention of the prosthesis along with fulfilling the functional demands of the patient.